Prevalence of Beijing and Haarlem genotypes among multidrug-resistant Mycobacterium tuberculosis in Iran: Systematic review and meta-analysis. (December 2017) - Tarashi, Samira; Fateh, Abolfazl; Jamnani, Fatemeh Rahimi; Siadat, Seyed Davar; Vaziri, Farzam
Abstract: Antimicrobial drug resistance creates major problems in the control of tuberculosis (TB). Beijing and Haarlem genotypes of Mycobacterium tuberculosis are the prevalent genotypes responsible for multidrug resistant (MDR) TB worldwide. The aim of this study was to conduct a systematic review using meta-analysis to indicate the prevalence of Beijing and Haarlem genotypes among MDR-TB cases in Iran. Data sources of current study were 311 original articles (2006–2016) that were searched in several databases including Medline, Scopus, Embase, Cochrane library, and Iranian databases. Sixteen articles were selected for the prevalence of Beijing and Haarlem families among MDR-TB strains. Data were evaluated using meta-analysis and random effects models with the Meta-Analysis Software package Version 2.2 (Biostat, Englewood, NJ). Final investigation indicated 856 MDR samples in the 16 articles. Overall, the prevalence of Beijing and Haarlem genotypes among MDR-TB isolates in Iran was estimated to be 19.3% (95% CI, 13.1–27.5) and 18.7% (95% CI, 11.9–28.3) respectively. The studies conducted in northern Iran showing a significant association between Haarlem genotype and MDR is of particular concern. Certain refugee migration flows make this genotype of particular epidemiological and clinical concern because of its potential ability to endanger TB control programs in Iran.